The Impact of Using the TGT Model Assisted by Wordwall Media to Improve Indonesian Language Learning Outcomes for Fifth Grade Students at SDN Pandian I - Amiliya Oktaviyana; Syaiful Bahri; Yeni Puji Astuti (SAINTIS Publishing, 2025)
This study investigates the impact of the Teams Games Tournament (TGT) model assisted by Wordwall media on improving the learning outcomes of fifth-grade students in Bahasa Indonesia at SDN Pandian I. The research employs a quantitative experimental method with a one-group pretest-posttest design involving 29 students. The results indicate a significant improvement in student learning outcomes, with pretest scores averaging 55% and posttest scores averaging 75%. Statistical analysis, including validity, reliability, normality, homogeneity, and hypothesis testing, confirms the effectiveness of the TGT model in enhancing student engagement and academic performance. The findings suggest integrating interactive media like Wordwall in cooperative learning models can foster a more engaging and effective educational environment.